Epidemiology and Treatment of Atrial Fibrillation - Cismaru, Gabriel; Andrew Chan, Keith (IntechOpen, 2020)
This book addresses the problem of atrial fibrillation in terms of epidemiology, risk factors, as well as treatment, including medical treatment using drugs, catheter ablation, and cardiac surgery. Most of the authors of the book are arrhythmologists, and chapters on atrial fibrillation are based on their experience in the cardiology clinic or the operating room.